Insulin Resistance Promotes the Formation of Aortic Dissection by Inducing the Phenotypic Switch of Vascular Smooth Muscle Cells - Zheng, Hui; Qiu, Zhihuang; Chai, Tianci; He, Jian; Zhang, Yuling; Wang, Chaoyun; Ye, Jianqiang; Wu, Xiaohui; Li, Yumei; Zhang, Li; Chen, Liangwan (Frontiers in Cardiovascular Medicine, 2022)
Background Insulin resistance (IR) plays a key role in the development of type 2 diabetes mellitus (T2DM) and is one of its most important characteristics. Previous studies have shown that IR and T2DM were independent risk factors for a variety of cardiovascular and cerebrovascular diseases. However, there are few studies on the relationship between IR and aortic dissection (AD). The goal of this research was to find evidence that IR promotes the occurrence of AD. Methods Through the statistical analysis, we determined the proportion of glycosylated hemoglobin (HbA1c) abnormalities (HbA1c > 5.7) in people with acute thoracic aortic dissection (ATAD) and compared the difference of messenger RNA (mRNA) and protein expression of GluT1 in the thoracic aorta of normal people and those with ATAD to find evidence that IR is a causative factor in AD. The mouse model of IR and AD and the IR model of human aortic vascular smooth muscle cells (HA-VSMC) were established. Real time-PCR (RT-PCR) and Western blotting were used to study the mRNA and protein expression. Hematoxylin and eosin (H&E), Masson, and elastic fiber staining, and immunofluorescence were used to study the morphological structure. Results The proportion of HbA1c abnormalities in patients with ATAD was 59.37%, and the mRNA and protein expression of GluT1 were significantly lower than that in normal people. Fasting glucose concentration (FGC), serum insulin concentration (SIC), and the homeostasis model assessment of insulin resistance (HOMA-IR) of mice was obviously increased in the high-fat diet group and the protein expressions of Glut1 and GluT4 were reduced, indicating that the mouse IR model was successfully established. The incidence of AD was different between the two groups (IR: 13/14, Ctrl: 6/14), and the protein expression of MMP2, MMP9, and OPN were upregulated and SM22 and α-SMA were downregulated in mice. The expressions of mRNA and protein of GluT1 and SM22 in HA-VSMCs with IR were reduced and OPN was increased. Conclusion Combined results of clinical findings, mouse models, and cell experiments show that IR induced the phenotypic switching of vascular smooth muscle cells (VSMCs) from contractile to synthetic, which contributes to the occurrence of AD. It provides a basis for further research on the specific mechanism of how IR results in AD and a new approach for the prevention and treatment of AD.